EVALUASI INVENTORY MANAGEMENT MENGGUNAKAN PERBANDINGAN MODEL EOQ DAN MODEL JIT PADA PT SHIELD ON SERVICE - Prayogi, Dika; Kustiningsih, Nanik (Fakultas Teknik Universitas Wisnuwardhana, 2021)
The purpose of this research is to determine which model is appropriate to use in inventory management at PT Shield On Service by comparing the Economic Order Quantity, Just In Time , and current methods applied to PT Shiel On Service. This type of research is qualitative research, in this study the data collection techniques carried out by researchers are literature study techniques and field observations. Meanwhile, the data that the researchers processed in this study were peimer and secondary data. In this study, the results showed that the use of the Economic Order Quantity and Just In Time models showed a value that was more efficient than the models used in companies today. Furthermore, between the Economic Order Quantity and Just In Time, modelsthemodel isJust In Time more efficient. If you use themodel you Economic Order Quantity can save 78%, while using themodel you Just In Time can save 70%. So it can be concluded that of the three models the Order Quantity economic model is the most efficient model.